2017
DOI: 10.18433/j3zd15
|View full text |Cite
|
Sign up to set email alerts
|

Ciprofloxacin does not Prolong the QTc Interval: A Clinical Study in ICU Patients and Review of the Literature

Abstract: Summary -Purpose. Ciprofloxacin may prolong the QT interval and increase the risk of Torsade de Pointes (TdP). Intravenous administration of ciprofloxacin in patients with additional risks may elevate the risk of QTc interval prolongation. We prospectively assessed whether intravenous ciprofloxacin prolongs the QT interval in patients with additional co-morbidities and risk factors. We also reviewed the literature on the QT prolonging effect or TdP inducing effect of ciprofloxacin. Methods. ICU Patients who we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
7
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 15 publications
3
7
0
2
Order By: Relevance
“…Таким образом, ципрофлоксацин, согласно актуальной информации, представляет собой фторхинолон с самым низким среди препаратов этой группы риском удлинения интервала QT [29,30]. По данным фармакоэпидемиологических исследований, ципрофлоксацин связывают с подобным синдромом в 0,3 случаев на 10 млн назначений, тогда как левофлоксацин -в 16 случаях, гатифлоксацин -в 27 случаях [19].…”
Section: Discussionunclassified
See 1 more Smart Citation
“…Таким образом, ципрофлоксацин, согласно актуальной информации, представляет собой фторхинолон с самым низким среди препаратов этой группы риском удлинения интервала QT [29,30]. По данным фармакоэпидемиологических исследований, ципрофлоксацин связывают с подобным синдромом в 0,3 случаев на 10 млн назначений, тогда как левофлоксацин -в 16 случаях, гатифлоксацин -в 27 случаях [19].…”
Section: Discussionunclassified
“…По данным фармакоэпидемиологических исследований, ципрофлоксацин связывают с подобным синдромом в 0,3 случаев на 10 млн назначений, тогда как левофлоксацин -в 16 случаях, гатифлоксацин -в 27 случаях [19]. В пользу отсутствия статистически значимого увеличения числа аритмий при монотерапии ципрофлоксацином бактериальных инфекций, в том числе у пациентов отделения интенсивной терапии в возрасте 60-85 лет, свидетельствуют результаты обзора литературы и клинического исследования, проведенных в 2017 г. голландскими исследователями [30].…”
Section: Discussionunclassified
“…Twelve lead Nihon Kohden's Cardiofax C electrocardiogram (Rosbach, Germany) and fasting blood glucose tests were obtained from each patient before starting antibiotic, after 24 hours, 72 hours from the first dose, and after 72 hours from antibiotic cessation. 22,23 QTc was automatically calculated by ECG device using Bazett's formula where QTc = QT/√(RR). 24 The borderline QTc range is 430-450 msec in males and 450-470 ms in females.…”
Section: F I G U R E 1 Follow-up Of the Study Patientsmentioning
confidence: 99%
“…Fluoroquinolones have been associated with heart abnormalities including Torsades de Pointus (TdP) which is a rare but lethal form of polymorphic ventricular tachycardia. There are reports on TdP associated with CIP [52]. It has also been suggested that CIP administration may contribute to tendon disorders [53].…”
Section: Introductionmentioning
confidence: 99%